Soil Quality and Heavy Metal Concentrations in Agricultural Lands around Dyeing, Glass and Textile Industries in Tangail District of Bangladesh - Tusher, TR; Piash, AS; Latif, MA; Kabir, MH; Rana, MM (Journal of Environmental Science and Natural Resources, 2018)
The study was conducted to investigate the soil quality including heavy metal concentrations in agricultural lands around dyeing, glass and textile industries at Tangail district of Bangladesh. A total of nine samples, three samples from each industrial site, were collected at a depth of 0-15 cm with an interval of 10 m from each point of the agricultural lands adjacent to selected industries for analyzing the soil chemical properties such as pH, OM, total N, available P and S including heavy metals (Pb, Cd, Ni, Cu and Cr) concentrations. The study found soil pH of 6.4 and 6.1 around textile and glass industry, respectively, while comparatively lower pH (4.4) was observed around dyeing industry. Comparatively higher levels of OM, total N, available P and S were found in soil around dyeing industry, whereas lower levels of OM and available S were observed around textile industry. The Cu, Pb and Cr were the dominant heavy metal around dyeing, glass and textile industry, respectively J. Environ. Sci. & Natural Resources, 10(2): 109-116 2017